INFLUENCE OF FERTILIZERS ON PHOTOSYNTHETIC AND PRODUCTION CAPABILITY OF WINTER WHEAT UNDER MODERATE HUMIDIFICATION - Alexander ЕSAULKO; Elena PISMENNAYA; Evgeny GOLOSNOY; Alena OZHEREDOVA; Vladimir KLETS (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The regulation of plants mineral nutrition using complex microfertilizers makes it possible to increase the productive capacity of wheat by optimizing physiological processes. Microelements that are part of enzymatic systems improve metabolism, contribute to the normal course of physiological processes that affect photosynthesis. Under the influence of microelements, the resistance of plants to diseases and adverse environmental conditions increases, the assimilation of macroelements from the soil and fertilizers improves. The lack of minor elements leads to a violation of the physiological processes in the plant's body and, as a result, a decrease in yield and a deterioration in its quality. The combination of various minor elements forms various types of microfertilizers. The goal of this research was represented by the microfertilizers Atlantica "Raikat Development", "All Inclusive", Wuxal "Microplant", Polidon "Complex", introduced on a different agricultural background (without fertilizers, recommended –N90P60 and calculated –N186P95K45). An integrated approach was used, carried out in 2020–2022 in the moderate moisture zone in the Central Ciscaucasia, based on the use of field measurements of the spectral properties of the winter wheat plants physiological state and laboratory studies of micro- and macroelements of fertilizers. A dispersion analysis of the indicators correlation reflecting the physiological state of plants, nitrogen and winter wheat yields was carried out on various agricultural backgrounds.